Africa’s virtual bridge between science and policy: Climate and Agriculture Network for Africa (CANA) platform - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
As a virtual interactive forum, CANA enables stakeholders from all over the world to engage in real time discussions on pertinent issues related to food security and nutrition in a changing climate. The platform continues to draw attention from partners and has the potential to expand scope to include e-courses.